Legionella: a reemerging pathogen. Issue 4 (August 2018) - Herwaldt, Loreen A.; Marra, Alexandre R.
Abstract : Purpose of review: The present review summarizes new knowledge about Legionella epidemiology, clinical characteristics, community-associated and hospital-based outbreaks, molecular typing and molecular epidemiology, prevention, and detection in environmental and clinical specimens. Recent findings: The incidence of Legionnaire's disease is rising and the mortality rate remains high, particularly for immunocompromised patients. Extracorporeal membrane oxygenation may help support patients with severe respiratory failure. Fluoroquinolones and macrolides appear to be equally efficacious for treating Legionnaires' disease. Whole genome sequencing is an important tool for determining the source for Legionella infections and for understanding routes of transmission and mechanisms by which new pathogenic clones emerge. Real-time quantitative polymerase chain reaction testing of respiratory specimens may improve our ability to diagnose Legionnaire's disease. The frequency of viable but nonculturable organisms is quite high in some water systems but their role in causing clinical disease has not been defined. Summary: Legionellosis remains an important public health threat. To prevent these infections, staff of municipalities and large buildings must implement effective water system management programs that reduce Legionella growth and transmission and all Medicare-certified healthcare facilities must have water management policies. In addition, we need better methods for detecting Legionella in water systems and in clinical specimens to improve prevention strategies and clinical diagnosis.